Impact of minimum wage on gender wage gaps in urban China - Shi Li; Xinxin Ma (IZA Journal of Labor & Development, 2015)
This paper provides evidence on whether the minimum wage (MW) has affected gender wage gaps in urban China. Several major conclusions emerge. First, from 1995 to 2007, the proportion of workers whose wages were below the regional MW level was greater for female workers than for male workers. Second, the results obtained by using the difference-in-differences estimation method show that from a long-term perspective, the MW will help to reduce gender wage gaps and that the effect is more obvious for the low-wage group. However, in the short term, the amelioration effect is not obvious.
Keywords: J31; J48; J71; 330; The minimum wage; Gender wage gap; Urban China